A Catalytic One-Pot Synthesis of Indolyl Cyclobutanones - Porcu, Stefania; Rodriguez, Carla Aira; Frongia, Angelo; Secci, Francesco (Synthesis, 2020)
A general strategy for the synthesis of indolyl cyclobutanones via a tandem Brønsted acid catalyzed 2-hydroxycyclobutanone activation–indole nucleophilic addition has been exploited. The procedure leads to a wide range of 2- and 3-functionalized indole derivatives in good to high yields with broad substrate scope.
Keywords: indoles; cyclobutanones; Brønsted acids; tandem reactions; catalysis